Providing a Model for Teaching Rhetoric to Arabic Language Students in Iraqi Universities Based on Ausubel’s Theory - Mahmood Dhahi, Raad; Shirzad Kebria, Baharak; Hussein Mukhlif, Mohsin; Saeidian Khorasghani, Narges (Assessment and Practice in Educational Sciences, 2025)
The present study aims to qualitatively analyze the educational experiences of Arabic language instructors in Iraqi universities and to examine the current status of rhetoric instruction within these institutions. This research adopts a qualitative approach and utilizes semi-structured interviews with 18 faculty members from departments of Arabic language and literature in both public and private Iraqi universities. Based on David Ausubel’s theory of meaningful learning, the study identifies three main dimensions in rhetoric instruction: cognitive organization, interactive and motivational strategies, and the transfer and application of rhetorical knowledge. Thematic analysis results revealed that the teaching of rhetoric in Iraqi universities faces several challenges, including the persistence of traditional teaching methods, limited integration of modern technologies, the lack of effective linkage between theoretical concepts and students’ prior experiences, and the absence of practical connections to real-life applications. The instructors emphasized the need for structured and gradual presentation of rhetorical concepts and for establishing meaningful connections between these concepts and students’ lived experiences in order to enhance instructional quality. The study proposes an instructional model based on Ausubel’s meaningful learning theory, which aims to transform rhetoric education from a purely theoretical process into a practical, engaging, and dynamic learning experience. Ultimately, the research recommends the adoption of innovative instructional models in Iraqi universities—particularly in the field of rhetoric education—that emphasize cognitive organization, interactive and motivational strategies, and the practical use of rhetorical knowledge.